2008
DOI: 10.5194/adgeo-13-37-2008
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the impact of transient luminous events on the atmospheric temperature

Abstract: Abstract. We present an order of magnitude estimate of the impact of sprites and other transient luminous events (TLEs) on the atmospheric temperature via ozone changes. To address the effects of expected TLE-ozone changes of at most a few percent, we first study the linearity of the radiatively driven response of a stratosphere-mesosphere model and of a general circulation model (GCM) to a range of uniform climatological ozone perturbations. The study is limited to Northern Hemisphere winter conditions, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…At this magnitude, sprite-NO x have detectable levels under favorable conditions. This confirms what is suggested by the analysis of satellite observations of NO x by Arnone et al [6,7], Rodger et al [21], and Arnone et al [5], with significant impact at local scale and negligible at global scale. At this magnitude of perturbation, any impact on the atmosphere would be negligible (see, e.g., [7]).…”
Section: Climate-chemistry Sensitivity To Tle-no Xsupporting
confidence: 88%
See 3 more Smart Citations
“…At this magnitude, sprite-NO x have detectable levels under favorable conditions. This confirms what is suggested by the analysis of satellite observations of NO x by Arnone et al [6,7], Rodger et al [21], and Arnone et al [5], with significant impact at local scale and negligible at global scale. At this magnitude of perturbation, any impact on the atmosphere would be negligible (see, e.g., [7]).…”
Section: Climate-chemistry Sensitivity To Tle-no Xsupporting
confidence: 88%
“…The coincidence window was chosen to be 60 min prior to MIPAS measurement, with horizontal dimensions of 500 km along latitude and 60 km along longitude, and a threshold of 10 WWLLN counts. Results by Arnone et al [6,7] over the period August-December 2003 showed a perturbation peak in the thunderstorm-NO 2 of about 1 ppbv (10 %) at 52 km altitude. An extension of this analysis up to April 2004 confirmed a significant change over latitudes 0-20 North (2-5 % at 52 km), with no significant change in ozone or other species.…”
Section: Thunderstorm Signatures In Mipas2d Nomentioning
confidence: 90%
See 2 more Smart Citations
“…Because of the modelled much smaller impact on ozone, direct perturbations to the radiativedynamics equilibrium of the upper atmosphere can be ruled out. This was also discussed by Arnone et al (2008a) with a calculation of the maximum temperature change induced by expected maximum ozone changes of the order of 1%. In the unrealistic case of total absence of transport, they calculated a maximum temperature change of 0.3 K within the ozoneperturbed air localized above extraordinary sprite-producing thunderstorms, an impact which reduces to 0.015 K in typical cases, i.e.…”
Section: Comparing Models and Observationsmentioning
confidence: 96%